Strigolactone biosynthesis is evolutionarily conserved, regulated by phosphate starvation and contributes to resistance against phytopathogenic fungi in a moss, Physcomitrella patens. Issue 2 (6th March 2017) - Decker, Eva L.; Alder, Adrian; Hunn, Stefan; Ferguson, Jenny; Lehtonen, Mikko T.; Scheler, Bjoern; Kerres, Klaus L.; Wiedemann, Gertrud; Safavi‐Rizi, Vajiheh; Nordzieke, Steffen; Balakrishna, Aparna; Baz, Lina; et al.
Summary: In seed plants, strigolactones (SLs) regulate architecture and induce mycorrhizal symbiosis in response to environmental cues. SLs are formed by combined activity of the carotenoid cleavage dioxygenases (CCDs) 7 and 8 from 9‐ cis ‐β‐carotene, leading to carlactone that is converted by cytochromes P450 (clade 711; MAX1 in Arabidopsis ) into various SLs. As Physcomitrella patens possesses CCD7 and CCD8 homologs but lacks MAX1, we investigated if PpCCD7 together with PpCCD8 form carlactone and how deletion of these enzymes influences growth and interactions with the environment. We investigated the enzymatic activity of PpCCD7 and PpCCD8 in vitro, identified the formed products by high performance liquid chromatography (HPLC) and LC‐MS, and generated and analysed ΔCCD7 and ΔCCD8 mutants. We defined enzymatic activity of PpCCD7 as a stereospecific 9‐ cis ‐CCD and PpCCD8 as a carlactone synthase. ΔCCD7 and ΔCCD8 lines showed enhanced caulonema growth, which was revertible by adding the SL analogue GR24 or carlactone. Wild‐type (WT) exudates induced seed germination in Orobanche ramosa . This activity was increased upon phosphate starvation and abolished in exudates of both mutants. Furthermore, both mutants showed increased susceptibility to phytopathogenic fungi. Our study reveals the deep evolutionary conservation of SL biosynthesis, SL function, and its regulation by biotic and abiotic cues.